1996
DOI: 10.1177/106591299604900211
|View full text |Cite
|
Sign up to set email alerts
|

New Research on Gendered Political Institutions

Abstract: This essay reviews four texts that analyze women in political institutions in order to develop a more general theory of gendered institutions. Scholar ship on women in political institutions will be advanced by continuing to look beyond the confines of the traditional subfields of political science, drawing on interdisciplinary work in feminist theory, critical race theory, and the sociology of work. Gender should be theorized, not as a word that is interchangeable with sex, but as a continuous, variable, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(73 citation statements)
references
References 13 publications
0
67
0
3
Order By: Relevance
“…In seeking an answer this question, we argue that it is imperative to take the parliamentary working environment into consideration -including not only formal regulations and procedures, but also informal practices, norms, and expectations. Previous research has revealed that political organizations, including legislative bodies, are often characterized by a culture of traditional masculinity, or institutional sexism, that empowers male legislators while placing female legislators at a disadvantage (Lovenduski, 2005, Kenney, 1996. That is to say that although formal rules and regulations no longer discriminate against women, power hierarchies, informal norms, practices, and expectations may still be gendered, thereby privileging men and masculine behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In seeking an answer this question, we argue that it is imperative to take the parliamentary working environment into consideration -including not only formal regulations and procedures, but also informal practices, norms, and expectations. Previous research has revealed that political organizations, including legislative bodies, are often characterized by a culture of traditional masculinity, or institutional sexism, that empowers male legislators while placing female legislators at a disadvantage (Lovenduski, 2005, Kenney, 1996. That is to say that although formal rules and regulations no longer discriminate against women, power hierarchies, informal norms, practices, and expectations may still be gendered, thereby privileging men and masculine behavior.…”
Section: Introductionmentioning
confidence: 99%
“…As Sapiro (1991) and Kenney (1996) explain, because American political institutions developed as male domains, these institutions are gendered, with men in the preferred position. ".…”
Section: Power Gender and Gatekeepingmentioning
confidence: 99%
“…Grasping the ways in which institutions reflect, reinforce, and structure unequal gendered power relations in wider society, in turn, offers insights into the dynamics of continuity and change -and the means for interrupting them to promote or undermine feminist goals. For FPS scholars, gender provides a central structuring dynamic of institutions, such that gender relations and gender norms are key legacies with which to contend in feminist analysis and strategies for political change (Mackay 2004: 112-113; see also Annesley and Gains forthcoming;Chappell 2002a;Duerst-Lahti 2002;Duerst-Lahti and Kelly 1995;Hawkesworth 2003;Kenney 1996;Kenny 2007;Lovenduski 1998Lovenduski , 2005bMackay and Meier 2003;Mackay 2008).…”
Section: See Also the Recent 'Critical Perspectives On Feminist Instimentioning
confidence: 97%